Hippocampal metabolism in preclinical Alzheimer's disease. (20th December 2022) - Rahmani, Maryam; McAvoy, Mark; Chang, Ryan; Raichle, Marcus E.; Benzinger, Tammie L.S.; Morris, John C.; Vlassenko, Andrei G.; Goyal, Manu S.
Abstract: Background: Hippocampal metabolism has been variably reported to be decreased in Alzheimer's disease (AD), and is less well studied during preclinical stages of AD. Since AD is associated with significant hippocampal atrophy, careful segmentation and partial volume correction methods are necessary. Here we performed manual segmentation of the hippocampus coupled with regional partial volume correction to estimate hippocampal glucose (rCMRGlc) and oxygen (rCMRO2 ) metabolism from positron emission tomography (PET) studies in cognitively normal adults with and without brain amyloid deposition. Method: Multi‐tracer PET including [ 18 F]fluoro‐deoxyglucose (FDG), 15 O‐O2, 15 O‐CO, and 15 O‐H2 O was performed in cognitively normal older adults with high brain amyloid‐β burden (n=17) and age and sex‐matched individuals with no brain amyloid burden (n=14). Hippocampi were manually segmented, including careful exclusion of intruding and surrounding CSF‐filled spaces. Partial volume correction was performed using the symmetric geometric transfer matrix approach. Mean standardized uptake value ratio (SUVR) for rCMRGlc and rCMRO2 were calculated, normalized to the whole brain and pons for confirmation. Results: We found no significant decrease in hippocampal rCMRGlc in amyloid positive adults, despite their lower hippocampal volume compared to amyloid negative adults. We also saw no significant decrease in hippocampal rCMRO2 in the amyloid positive adults. These results were unaffected by choice of whole brain or pons as the reference region. Conclusion: Hippocampal metabolism appears to be relatively preserved in cognitively normal amyloid positive adults. Reported alterations in hippocampal metabolism might therefore be more closely linked to the onset and progression of cognitive impairment.